ANALISIS UNJUK KERJA COOLING TOWER INDUCED DRAFT COUNTER FLOW DENGAN BAHAN PENGISI ASBES - Fachriza Putra Pratama; Digdo Listyadi Setyawan; Mochamad Edoward Ramadhan (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2021)
Industrial development is one of the economic components that influences national economic growth. Increased industrial growth is also aimed at realizing national goals for the welfare of society. In the industrial process, the machine generates heat as a side effect of the machine's work, so it requires a cooling system for its continued work. The facilities used by the industry to overcome these problems are by using cooling towers. One of the factors that influence the cooling tower performance is the filler. Asbestos is a material that has a thin and corrugated sheet shape. This material is made of the mineral silica and fine fibers. Asbestos material has many benefits and roles in industrial activities. The purpose of this study was to determine the effect of asbestos filler on cooling tower performance induced draft counter flow on the effect of variations in initial water temperature and air velocity, and the effect of effectiveness, water-air ratio, cooling capacity, evaporation loss and L / G value. This research on the performance of cooling towers with asbestos fillers obtained a higher value of effectiveness and cooling capacity than cooling towers without using fillers. This is evidenced by the highest value of effectiveness obtained by cooling towers using fillers of 83.26%, while the highest value for cooling towers without using fillers is 80.24%. The highest value of cooling capacity in a cooling tower using filler material is 10.34 kJ / s, while the highest value for a cooling tower without using a filler is 9.70 kJ / s. Keywords: Asbestos, Cooling tower, Industry